Impact of Late Ventricular Arrhythmias on Cardiac Mortality in Patients with Acute Myocardial Infarction - Takuma Takada; Koki Shishido; Takahiro Hayashi; Shohei Yokota; Hirokazu Miyashita; Hiroaki Yokoyama; Takashi Nishimoto; Tomoki Ochiai; Noriaki Moriyama; Kazuki Tobita; Shingo Mizuno; Futoshi Yamanaka; et al. (Journal of Interventional Cardiology)
Objectives. This study investigated the relationship between the timing of ventricular tachycardia or ventricular fibrillation (VT or VF) and prognosis in patients undergoing primary percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI). Background. It is unknown whether the timing of VT/VF occurrence affects the prognosis of patients with AMI. Methods. From January 2004 to December 2014, 1004 patients with AMI underwent primary PCI. Of these patients, 888 did not have VT/VF (non-VT/VF group) and 116 had sustained VT/VF during prehospitalization or hospitalization. Patients with VT/VF were divided into two groups: early VT/VF (VT/VF occurrence before and within 2 days of admission, 92 patients) and late VT/VF (VT/VF occurrence >2 days after admission; 24 patients) groups. Results. The frequency of VT/VF occurrence was high between the day of admission and the 2nd day and between days 6 and 10 of hospitalization. The late VT/VF group had a significantly longer onset-to-balloon time, lower ejection fraction, poorer renal function, and higher creatine phosphokinase (CK)-MB level on admission (p< 0.001). They also had a lower 30-day cardiac survival rate than the early VT/VF and non-VT/VF groups (42% vs. 76% vs. 96%, p < 0.001). Moreover, independent predictors of in-hospital cardiac mortality among patients with AMI who had sustained VT/VF were higher peak CK-MB [Odds ratio (OR: 1.001, 95%confidence interval (CI): 1.000-1.002, p= 0.03)], higher Killip class (OR: 1.484, 95%CI 1.017-2.165, p= 0.04), and late VT/VF (OR: 3.436, 95%CI 1.115-10.59, p= 0.03). Conclusions. The timing of VT/VF occurrences had a bimodal peak. Although late VT/VF occurrence after primary PCI was less frequent than early VT/VF occurrence, patients with late VT/VF had a very poor prognosis.